Komunikacja taktyczna jako skuteczne narzędzie do zapewniania bezpieczeństwa członków zbiorowości .......... 81 - Jurczak, Dominik (Systemy bezpieczeństwa: Wymiar lokalny i państwowy, 2020)
The experience derived from securing public events shows that usage of the Tactical Communication presents a possibility of aggression de-escalation, averts grouping in large quantities, as well as prevents unforeseen behaviours including panic. Such a model also allows to decrease a level of hostility from groups presenting negative attitude towards law enforcement services and assists with effective gathering of information regarding their intentions by increasing attention to a feedback.